Collaborative Pentahelix Model In Overcoming Stunting Anomalous Increase In Stunting Rate In Bengkulu Province - Edriwan Mansyur; Julius Habibi; Umi Badriyah; Supardi Supardi; Hartian Pansori (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Stunting is a national problem that is still a concern because it relates to the nutritional condition of toddlers as the nation's next generation. The Bengkulu Province Government launched the Pentahelix collaboration involving five elements: academia, business, communities, government, and media, to reduce stunting rates. This study aims to identify, describe, and analyze the collaboration of the pentahelix model in accelerating the reduction of stunting in Bengkulu Regency. The type of research used in this research is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The data analysis technique consists of four analysis components: data collection, data condensation, data presentation, and drawing conclusions or verification. Based on the research results, the five pentahelix elements contribute according to their respective functions. The implementation of collaboration is Several elements in Pentahelix still have obstacles in terms of implementing collaboration between related stakeholders. So, the advice that can be given for implementing this collaboration is that the TJSL Forum as a business element is expected to immediately contribute to the stunting problem in Bengkulu Province. As part of the pentahelix, the community is expected to play a more active role in becoming cadre members to minimize delays in data collection and management. Social media should be improved for consistency in posting health content about stunting.